"مدح السعي وذم البطالة" لأبن كمال باشا ت. 940هـ.: دراسة وتحقيق - أبو الحاج، صلاح محمد سالم (مجمع الفقه الإسلامي بالهند, 2016)
هذه رسالة مختصرة لأحد شيوخ الإسلام في الدولة العثمانية، ابن كمال باشا (ت 940ه)، تحدثت فيها عن قضية الكسل التي يعاني منها أكثر الناس، ولا سبيل للإنسان للنجاح في حياته وأخرته إلا بالتخلص منها، حيث سلك المؤلف فيها منهجا لطيفا في توضيح الفكة بذكر الآيات والآثار والأحكام التكليفية ونقولات عن بعض الحكماء، وهي مع شدة اختصارها اشتملت على معاني وفوائد عديدة مما دفعني للعناية بها وتحقيقها ليعم وينتشر بين الباحثين، وقدمت لها بترجمة قصيرة عن المؤلف، ودراسة عن الرسالة، وعلقت عليها بما تحتاجه من توضيح.
This brief message to one of the elders of Islam in the Ottoman Empire, Ibn Kamal Pasha (d. 940 AH), in which I spoke about the issue of laziness experienced by most people and there is no way for a person to succeed in life unless he get rid of it, where the author approach a nice way to clarify the idea by citing the qura`n verses, prophetic tradition, and sayings of some scholars. which is with the severity shortened included many benefits and meanings which prompted me to take care of them and study them to prevail and spread among researchers. I presented it with a short translation of the author, and a study of the letter. I commented on what it need to be clarified.
Keywords: ابن كمال، أحمد بن سليمان، ت. 940 هـ. -- الاسلام والعمل -- الاسلام والبطالة -- والاداب الاسلامية